Fault identification in power cables by using travelling wave-based approach - et. al., M.NagaJyothi, N.Mounika, B.Puneeth,T.Haripriya (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Thefaults in the underground cables cause to generatetransients which propagate along the power cable as travelling waves. The velocity of the generated travelling wave and the time taken by a wave to reach the source point from the fault location enables us to calculate the fault distance value.In this paper a double endedtravelling wave based approach is used and a communication channel is designed to calculate the fault distance. A circuit-based model is developed in the EMTP-RV software to find out the fault distance from the source end for all types of faults. Further it is proved that the fault distance is unaffected by the change in ground resistance, various types of faults and the fault inception angle in the proposed method